Mood and Cognition in Old Age - Lia Fernandes (Frontiers Research Topics, 2018)
Improving psychological well-being and cognitive health is now listed as the priority on the healthy aging agenda. Depression and cognitive impairment are great challenges for the elderly population. There have been numerous studies on depression and cognitive impairment and dementia. However, the neural correlates of depression and cognitive impairment have not yet been elucidated. With the development of neuroscience and relevant technologies, studies on anatomical and functional neural networks, neurobiological mechanisms of mood and cognition in old age will provide more insight into the potential diagnosis, prevention and intervention in depression and cognitive impairment. For example, longitudinal neuroimaging studies depicting the trajectories of patterns of structural and functional brain networks of mild cognitive impairment may provide potential imaging markers for the onset of dementia. Population-based studies have addressed the potential interaction between mood and cognitive impairment in old age. However, there are few studies to explore the potential neural mechanism of the relationship between depression and cognitive impairment in old age. In all of this process the contribution of multiple biological events cannot be neglected, particularly the underlying influence of chronic diseases and concomitant polymedication as well as the geriatric conditions, like frailty, frequently present in this elderly population, which also compromise the cognitive function and mood determining depression and conducing to worse outcomes with more morbidity and mortality.